Clinical characteristics, treatment, and wound management of pyoderma gangrenosum: A case series. - Feixia Wang; Lu Li; Weizhen Li; Xiaobo Ni; Zhe Pan; Lingling Ying; Mina Zhu (PLoS ONE)
Objective This study aimed to evaluate the clinical characteristics, diagnostic processes, therapeutic approaches, and wound management strategies for patients diagnosed with pyoderma gangrenosum (PG), a rare inflammatory skin condition often resulting in misdiagnosis and treatment delays. Methods A case series was conducted involving patients diagnosed with PG at the author's Hospital, from January 1, 2020 to April 3, 2023. Data on patient demographics, wound characteristics, treatment methodologies, and wound care experiences were collected and analyzed. Results The study included nine male patients with a mean age of 48.6 years (median 50 years). All patients were initially misdiagnosed, predominantly as skin infections or cellulitis. Lesions were mainly located on the lower extremities, with ulcerative PG being the most common subtype. Seven patients had skin injuries preceding PG onset. Treatment included systemic glucocorticoids and comprehensive wound care approaches. Three patients required additional interventions, like negative pressure wound therapy. Ultimately, six patients healed, while three died due to severe comorbidities or septic shock. Conclusion PG is frequently misdiagnosed and often presents as ulcerative lesions triggered by skin injuries. Effective management, including systemic glucocorticoids and focused wound care, can significantly improve patient outcomes.